OPTIMIZING THE USE OF INSTAGRAM TO ENHANCE B2B LEAD GENERATION : A CASE STUDY OF TELKOM DWS - Muthia Rizqika Fatiha; Nila Armelia Windasari (LPPM STIE Muhammadiah Bandung, 2026)
Social media is widely employed in B2B marketing, especially in wholesale telecoms, where technical and professional audiences are targeted. Telekom DWS employs Instagram for digital marketing, although its impact on early-stage audience interest and leads is unknown. Instagram content attracted B2B audiences and generated early leads in this study. The study employed sequential explanatory mixed methods. The Wilcoxon Signed-Rank test compared Product, People, Perspective, and Progress content categories in initial quantitative analysis. Results were qualitatively gathered from in-depth interviews with internal lead management and marketing stakeholders. Instagram performance metrics and interview data were thematically evaluated. No significant differences were found in Wilcoxon analysis at the α = 0.05 level. According to the new trend, perspective content, which provides educational and industrial insights, outperformed product content in profile views, indicating early-stage interest. Similar to commercial postings, progress material had more audience interaction. Interviews show that target demographics like new Internet service providers (ISPs), IT organizations, and digital enterprises value industry context, expertise, and relevance to wholesale services over promotional messages. The research identified operation issues despite excitement.Attention-grabbing instructional and insight-driven information has limited impact. Human ability, lead classification, and the lack of an integrated tracking dashboard prevent early curiosity from becoming commercial promise. In addition to content development, an organization's internal preparedness to respond to audience interaction affects Instagram's business-to-business power. An organized and responsive lead management system must support an informative and credibility-focused content strategy to maximize Instagram's lead pipeline role. Telkom DWS uses this study to implement sustainable recommendations and content-based digital marketing strategies for B2B, especially wholesale telecommunication industry.